The polyethylene terephthalate water bottles problem in Dubai hotels—Would an initiative solve this problem or does it need a law? - Al-Shihabi, Sameh (Frontiers in Sustainable Cities, 2023)
This paper examines the environmental effects of polyethylene terephthalate (PET) water bottles used by tourists in Dubai. Unfortunately, tourists residing in Dubai hotels must depend on these single-use plastic water bottles that have negative environmental impacts associated with their production and disposal. Thus, the government of Dubai launched an initiative to reduce the usage of PET bottles, and this paper discusses whether this initiative is adequate to change hotels' dependence on PET water bottles. Therefore, this paper tries first to find the reasons that would drive hotels to comply with this initiative and then assesses the compliance of hotels with this initiative one year after its launch. It is found that pressures from hotels with the same and higher ratings are crucial drivers for hotels to replace PET bottles with other alternatives. Officials affiliated with the Dubai Can initiative confirmed these findings. They have also anticipated that UAE residents who spend their vacations in Dubai hotels will exert substantial pressure on hotels to abandon PET bottle use. Decision-makers affirmed that a good percentage of five-star hotels, in addition to several four-star hotels, have abolished the use of PET bottles. Moreover, it is anticipated that all hotels are expected to stop using PET bottles. Consequently, this study shows that promoting environmentally responsible behavior without enacting laws is possible.